15 hz Electroacupuncture at St36 Improves Insulin Sensitivity and Reduces Free Fatty Acid Levels in Rats with Chronic Dexamethasone-Induced Insulin Resistance. Issue 4 (August 2016) - Tzeng, Chung-Yuh; Lee, Yu-Chen; Chung, Jui-Jung; Tsai, Jen-Chieh; Chen, Ying-I; Hsu, Tai-Hao; Lin, Jaung-Geng; Lee, Kuan-Rong; Chang, Shih-Liang
Objective: To evaluate the effect of electroacupuncture (EA) in a rat model of chronic steroid-induced insulin resistance (SIIR). Methods: An SIIR rat model was created using daily intraperitoneal injections of clinically relevant doses of dexamethasone (1 mg/kg) for 5 days to induce chronic insulin resistance. Thirty-six SIIR rats were randomly divided into the SIIR+EA group (n=18), which received 15 Hz EA at ST36 for 60 min, and the SIIR group (n=18), which remained untreated. Plasma glucose and free fatty acid (FFA) levels were measured in serial blood samples taken without further manipulation (n=6 per group) and during insulin challenge test (ICT, n=6 per group) and intravenous glucose tolerance test (ivGTT, n=6 per group). Insulin receptor substrate (IRS)-1 and glucose transporter (GLUT)-4 were measured using Western blotting and expressed relative to β-actin. Results: Following EA, area-under-the-curve (AUC) for glucose was reduced (7340±291 vs 10 705±1474 mg/dL/min, p=0.049) and FFA levels significantly lower at 30/60 min in the SIIR+EA versus SIIR groups. Similar effects on glucose AUC were seen during the ICT (5568±275 vs 7136±594 mg/dL/min, p<0.05) and igVTT (11 498±1398 vs 16 652±1217 mg/dL/min, p<0.01). FFA levels were lower at 30 and/or 60 min in SIIR+EA versus SIIR groups (p<0.01). Relative expression of IRS-1 and GLUT4 were significantly increased by EA (p<0.01). Conclusions: EA decreased the FFA level and increased insulin sensitivity in SIIR rats. Further clinical studies are needed to determine whether EA is an effective alternative treatment for the reduction of insulin resistance in patients requiring chronic use of dexamethasone.